On the decline of war - Michael Spagat; Stijn van Weezel (University College Dublin, UCD School of Economics, 2018)
For the past 70 years, there has been a downward trend in the size of wars, but the idea of an enduring "long peace" remains controversial. Some recent contributions suggest that observed war patterns,including the long peace, could have come from a long-standing and unchanging war-generating process, an idea rooted in Lewis F Richardson's pioneering work on war. Aaron Clauset has tested the hypothesis that the war sizes after the Second World War are generated by the same mechanism that generated war sizes before the Second World War and fails to reject the "no-change" hypothesis. In this paper, we transform the war-size data into units of battle deaths per 100,000 or world population rather than absolute battle deaths - units appropriate for investigating the probability that a random person will die in a war. This change tilts the evidence towards rejecting the no-change hypothesis. We also show that sliding the candidate break point slightly forward in time, to 1950 rather than 1945, leads us further down the path toward formal rejection of the no-change hypothesis. Finally, we expand range of wars to include not just the inter-state wars considered by Clauset (2018) but also intra-state wars. Now we do formally reject the no-change hypothesis. Finally, we show that our results do not depend on the choice between two widely used war datasets.
Keywords: C10; D74; N40; 330; War; rare events; binomial probability